PENGARUH VARIETAS DAN BAHAN ORGANIK TERHADAP JUMLAH ANAKAN DAN PRODUKSI PADI SAWAH IP 400 FASE VEGETATIF MUSIM TANAM I - Timbul Simbolon; Posma Marbun; Fauzi Fauzi (Universitas Sumatera Utara, 2013)
This research was aimed to determine whether composting organic materials and varieties of riceplants of different IP 400 can reduce the rate of air temperature in rice vegetative phase and also toknow which varieties or organic matter are likely to be better in reducing the rate of air temperatureand increase rice production IP 400. This research was conducted in paddy fields and DevelopmentResearch Institute, Village Market District Leaning Fence Merbau Deli Serdang (30 29 '51.33